PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION TERHADAP PEMAHAMAN KONSEP DAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Sutinah (Pendidikan Matematika | STKIP YM Bangko, 2018)
Based on the results of the initial test it is known that understanding concepts and mathematical problem solving abilities of students is still low. This can be seen from three indicators of understanding concepts and mathematical problem solving abilities that are not achieved by students. One reason is that teachers only use conventional learning. This study aims to find out and describe the understanding of concepts and mathematical problem solving abilities taught with cooperative learning model group investigation type better than those taught with conventional learning class VIII students of SMP Negeri 12 Merangin 2017/2018 Academic Year. Based on the results of test data analysis the understanding of mathematical concepts is obtained, = greater than = 1.675. then analysis of test data obtained by mathematical problem solving abilities = greater than = 1,675 then rejected. From these results it can be concluded that the understanding of concepts and mathematical problem solving abilities taught by cooperative learning model group investigation type is better than conventional learning of class VIII SMP Negeri 12 Meragin 2017/2018 Academic Year. Keywords: Understanding of mathematical concepts, mathematical problem solving ability, Type Cooperative Study Model Group Investigation